An accurate prospect of Vienna, the capital of Germany - Hawkins (engraver):::Creator::::::::::::; Millar, George Henry (author):::Contributor:::::::::::: (United Kingdom; London; Alexander Hogg)
Engraving with panoramic view of Vienna from across the Danube, with a peasant and farm animals in the foreground.